Centro culturale: Fonte Mazzola, Peccioli (Pisa) - Heliopolis 21 (AND Rivista di architetture, città e architetti, 2019)
In Tuscany, in the countryside sur- rounding the town of Peccoli, the Heliopolis 21 studio carried out the reconstruction of a 19th century rural building, now completely reduced to ruins.